THE QUALITY OF CHICKEN EGG RACES THAT STORED FOR 14 DAYS IN VARIOUS EGG STORAGES - M., Ulfa; Wiyana, I K. A.; Wirapartha, M. (Jurnal Peternakan Tropika, 2018)
This study aims to determine the effect of various ingredients of chicken egg storage such as wire box, egg tray carton, and wooden box on the external and internal quality of eggs kept for 14 days. This research was carried out at Poultry Livestock Laboratory of Faculty of Animal Husbandry, Udayana University for three weeks of March 19th until April 8th, 2018. This research used Completely Randomized Design (CRD) with 3 treatment which based on egg tray carton (T), wire box (K), and wooden box (W) consists of 6 replications. Each replication consists of 5 eggs, so the eggs are used as much as 90 grains. Variable that we observed based on external quality include egg weight and egg shape index, as well as internal quality which include eggshell thickness, eggshell weight, egg yolk, egg white height, pH and HU (Haugh Unit) egg. The results show indicate that egg tray carton storage has significantly lower apparent eggshell (P<0.05) than wire box. The storage of wire box eggs and wooden boxes had significantly lower actual HU egg yields (P<0.05) than egg tray carton. Against egg weight, egg shape index, shell thickness, egg yolk, high egg white and egg pH, egg storage did not give significantly different results ??(P>0.05). Based on the result of the research, it can be concluded that the chicken eggs from egg tray carton has HU (Haugh Unit) and eggshell weight is better than chicken egg that is stored on wire box and wooden box for 14 days storages. : chicken egg races, egg storages, egg quality, long storages